(untitled) (International Congress on Economics, Management and Business Studies, 2026)
This article analyzes the specific features of translating terms used in English scientific texts from a linguistic perspective. The study examines structural, semantic, and functional aspects of terms, as well as the problems and strategies involved in translating them into Uzbek. The results show that terminological accuracy, contextual appropriateness, and equivalence are the main criteria of translation.